Medicine for Dental Students - Alagappan (jaypee, New Delhi, 2004)
The second edition of Medicine for Dental Students is a unique combination of clinical methods with the text fully revised and updated. More number of clinical photographs, diagrams and tables have been added to aid the students for proper clinical examination and learning. Two new chapters Substance Abuse and Imaging Modalities in Internal Medicine have also been added. Prof R Alagappan has served in the teaching faculty of Tamil Nadu Medical Services for nearly three decades as Assistant Professor of Medicine, Lecturer, Medical Registrar, Professor of Therapeutics, Professor of Medicine and finally retired as Director Professor and Head of the Institute of Internal Medicine, Madras Medical College and Senior Physician, Government General Hospital. He has been the examiner for both undergraduates and postgraduates in many southern universities. He is a fellow of Indian College of Physicians. He is also a Life Member in Diabetic Association of India, Geriatric Society of India, National Council on Hypertension and Indian Society of Clinical Pharmacology and Therapeutics. Prof. Alagappan has presented more than 75 scientific papers in many regional and national conferences. He has also conducted many regional and national conferences besides several continuing Medical Education Programmes. He is the author of the popular medical book Manual of Practical Medicine.
14. Imaging Modalities in Internal Medicine.
Dental Students
Keywords: Dentistry -- Medicine